PENGARUH INTENSITAS PERSAINGAN PASAR TERHADAP PENGGUNAAN INFORMASI BENCHMARKING DAN MONITORING DAN KINERJA MANAJER UNIT BISNIS - FAISAL; TRI JATMIKO WAHYU PRABOWO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2005)
Managers’ use of the information provided by management accounting system (MAS) can help organizations to adopt and implement plans in response to their competitive environment. In this research MAS is viewed as a system which provides benchmarking and monitoring information in addition to internal and historical information traditionally generated by management accounting system. This research examines the mediating role of managers’ use of benchmarking and monitoring information in the relationship between the intensity of market competition and business unit performance. This research based on the previous research by Mia and Clarke (1999). Data of this research was collected via mail survey to 72 production and marketing managers. Data was analyzed using path analysis. The results of this research supported the result of The Australian Financial Review (1995) but failed to support Mia and Clarke (1999) revealed that increasing intensity of market competition is associated with increasing managers use of the MAS information (benchmarking and monitoring) and increasing managers use of the MAS information increasing business unit performance.